The Role of Victim’s Assistant to Prevent Secondary Victimization : Case Women Victim of Marital Rape - Jenny Rahayu Afsebel Situmorang; Vinita Susanti (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
Women (wives) is the most hidden victim of marital rape. Regarding this issue, we argue that women victims need victim assistance to prevent secondary victimization. This article is based on a literature review with a qualitative approach. Turning to marital rape cases in Indonesia, women's victims get harmful impacts in physiological and physical. Women victims of marital rape in Tanjung Priok, Bali, Pasuruan, and